Mitochondrial regulation of oxygen sensing - Chandel, Navdeep S (Advances in experimental medicine and biology, 2010)
Hypoxia promotes physiological processes such as energy metabolism, angiogenesis, cell proliferation, and cell viability through the transcription factor Hypoxia Inducible Factor (HIF). Hypoxia also diminishes the activity of ATP consuming processes to promote cell survival. The mechanism(s) by which hypoxia activates HIF and diminishes ATP demand are a subject of intensive research. Here we outline the model in which mitochondrial complex III regulate the activity of HIF and diminish ATP utilization processes through the increased production of ROS during hypoxia.